Pulmonary Infection - Pokorski, Mieczyslaw.; Pokorski, Mieczyslaw. (Neuroscience and Respiration, 2015)
The respiratory tract is a frequent target of infections caused by a wide range of organisms. The book provides reader-friendly information on aspects of pulmonary infections, including comprehensive accounts of bacterial and viral diseases, therapeutic approaches, molecular and classical culture-related techniques of diagnosis, and explaining the basic cell biological mechanism. The role of oxidative stress, both helpful in fighting invading pathogens and detrimental in yielding to infection is detailed as it is often undervalued and needs focus. The chapters encompass latest developments and applications in bacteriology and virology, preventive and therapeutic tips, and raise attention to implementation of proper antibiotic policies by medical institutions to decrease resistance to antimicrobials. The perennial problem of low influenza vaccination coverage rate is rationalized. The volume will be of interest to both clinicians and biomedical researchers engaged in this exciting field.